Amelioration of aging-induced muscular decline by black soybean (Rhynchosia nulubilis) and black rice (Oryza sativa L.) extracts - Park, Hyejeong; Yu, Seungmin; Kim, Wooki (Frontiers in Immunology, 2025)
Aging leads to a decline in the mass and function of skeletal muscles, a condition known as sarcopenia. It was previously reported that aging-related alterations in protein degradation, chronic inflammation, and deterioration of mitochondrial metabolism affect the acceleration of muscle atrophy in the elderly. However, the detailed mechanism or substantial causes for age-related muscle loss are still lacking, yet exercise or an increment in dietary protein intake are suggested as effective approaches to mitigate muscle atrophy. This study aims to investigate the regulatory effect of black soybean (Rhynchosia nulubilis) and black rice (Oryza sativa L.) mixture extract (BBME), which are rich in protein and bioactive compounds, in 12-month-old aged mice and L6 myotubes. BBME was orally administered at 300 and 600 mg/kg/day (low and high doses) for 12 weeks, and its effects on systemic glucose homeostasis and skeletal muscle metabolism were evaluated. Consequently, BBME at a high dose marginally ameliorated muscle loss and significantly improved glucose metabolism. BBME also reduced cellular senescence markers and enhanced mitochondrial biogenesis in aged skeletal muscles. Additionally, BBME exerted insulin-like activity by promoting glucose metabolism in L6 myotubes. These findings suggest the potential of BBME as a functional food ingredient in alleviating aging-induced muscle loss by modulating mitochondrial activity and glucose metabolism.